Rhus verniciflua stokes extract, a traditional herbal medicine, combined with first-line chemotherapy for unresectable locally advanced and metastatic pancreatic cancer: a prospective observational pilot study - Jin, Hayun; Lee, Su Hyeon; Kim, Eun Hye; Park, Su Bin; Park, Namyoung; Joo, Kwang Ro; Yoon, Seong Woo (Frontiers in Oncology, 2024)
Pancreatic cancer is among the most lethal cancers with limited treatment options. Traditional herbal medicines have been explored as potential adjunct therapies for enhancing the effectiveness of standard chemotherapies. In this study, we investigated the safety and efficacy of Rhus verniciflua Stokes (RVS) in combination with first-line chemotherapy for unresectable locally advanced and metastatic pancreatic cancer in a prospective setting. This prospective observational pilot study enrolled patients with confirmed inoperable stage III or IV pancreatic cancer undergoing or scheduled to receive 5-fluorouracil-based or gemcitabine-based first-line chemotherapy with RVS treatment and were followed up for up to 20 months. The primary endpoint was the safety profile of RVS, which was assessed through adverse events. The secondary endpoints included overall response rate (ORR), disease control rate (DCR), progression-free survival (PFS), and overall survival (OS). Cox regression analysis identified possible prognostic factors for PFS and OS. Of the enrolled 25 patients, 18 completed the follow-up. The median RVS treatment duration was 6.14 months (range 2.23–8.01 months) and the median RVS daily dose was 3.8 capsules/day (range 2.1–5.7 capsules/day). RVS showed a favorable safety profile, with only one case of non-severe pruritus possibly related to RVS treatment. No hepatotoxicity and nephrotoxicity related to RVS was reported. The ORR and DCR were 5.6% and 72.2%, respectively. The median PFS and OS were 7.24 months (95% CI: 3.15–12.9) and 13.9 months (95% CI: 1.14–27.72), respectively. Cox regression analysis showed that baseline CA19-9 level was an independent prognostic factor for OS, and the daily dose of RVS was an independent prognostic factor for PFS and OS. In conclusion, RVS can be administered safely to patients with unresectable locally advanced metastatic pancreatic cancer who are undergoing first-line chemotherapy, and the daily dose was an independent prognostic factor for cancer survival. Further randomized controlled studies are warranted to confirm the exact benefits of RVS treatment.Clinical trial registrationhttps://cris.nih.go.kr, identifier KCT0007496.